Nested Sub-System Model of Technostressors: Impact of Psychological Need Satisfaction, Technostress Inhibitors, Mindfulness and LMX Quality on Burnout and Work Engagement - Ramesh, Rofia (Curtin University, 2022)
This thesis examines the impact of a nested sub-system of technostressors on burnout and work engagement. It also investigates psychological need satisfaction (PNS) as a mediator and technostress inhibitors, components of mindfulness, and LMX quality as moderators. Using survey data from 653 respondents, a Structural Equation Modelling analysis was conducted. The results support the nested sub-system model and mediation by PNS. Partial support was obtained regarding moderation by components of mindfulness.